Headache and internet addiction: a narrative review - Rangel, Tathiana Corrêa; Rocha-Filho, Pedro Augusto Sampaio (Headache Medicine, 2018)
Background: Among young people, headache-related impairments imply inability, failure and school absenteeism, as well as greater vulnerability to comorbidities. Based on this, the intensive mobile phone and computer use were associated to unhealthy habits. Previous researches reinforce the predictive validity regarding the influence of internet dependence on physical conditions, emotional behavior and quality of life of young people. Few studies associate internet abuse with headache prevalence. Material and Methods: This study was a narrative literature review. Results: Excessive computer and technological instruments use is considered to have a negative impact on physical health and may be associated to somatic